2009
DOI: 10.1016/j.cub.2009.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Activation By Honey Bee Queen Pheromone

Abstract: Queen mandibular pheromone (QMP) is produced by honey bee queens and used to regulate the behavior and physiology of their nestmates. QMP has recently been shown to block aversive learning in young worker bees, an effect that can be mimicked by treating bees with one of QMP's key components, homovanillyl alcohol (HVA). Although the mechanisms underlying this blockade remain unclear, HVA has been found to lower brain dopamine levels and to alter intracellular levels of cAMP in brain centers involved in learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 24 publications
2
67
0
Order By: Relevance
“…One of QMP's key components, homovanillyl alcohol (HVA), selectively activates the D2-like dopamine receptor, AmDOP3 (20). Although it is known that AmDOP3 receptors are expressed in the brain (21), we examined the possibility that this QMP-activated receptor may be expressed also in the antennae of the bee.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of QMP's key components, homovanillyl alcohol (HVA), selectively activates the D2-like dopamine receptor, AmDOP3 (20). Although it is known that AmDOP3 receptors are expressed in the brain (21), we examined the possibility that this QMP-activated receptor may be expressed also in the antennae of the bee.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of AmDOP3 receptors, either by dopamine or by the QMP component, homovanillyl alcohol, inhibits accumulation of the intracellular signaling molecule, cAMP (20,21), an effect that is likely to inhibit signaling via the D1-like dopamine receptors, AmDOP1 and AmDOP2. Dopamine signaling in the antennae could potentially be further inhibited by QMP-induced changes in levels of dopamine receptor gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only one OA receptor gene, Amoa1, has been characterized and identified in this region of the brain (Grohmann et al 2003); however, several putative OA receptors have been identified in the honeybee genome (Hauser et al 2006) and are currently being characterized. Amdop1, Amdop2, and Amoa1 code for G-protein-coupled receptors that increase intracellular levels of cAMP when activated (Blenau et al 1998;Grohmann et al 2003;Humphries et al 2003;Mustard et al 2003Mustard et al , 2005Beggs and Mercer 2009), whereas activation of the AmDOP3 receptor generally reduces intracellular levels of cAMP Clark and Baro 2007;Beggs and Mercer 2009). Increases in cAMP levels resulting from AmDOP3 receptor activation can be observed also under some conditions (Clark and Baro 2007), and AmOA1 receptors and the dopamine receptor, AmDOP2, signal not only via cAMP but also through changes in intracellular Ca 2+ (Grohmann et al 2003;Beggs et al 2011).…”
mentioning
confidence: 99%
“…Indeed measurements of global responses of receptor neurons in the antennae of the bee have shown that antennal receptors are responsive to all five of the key components of QMP (Brockmann et al 1998). Evidence suggests, however, that the aromatic compounds HOB and HVA may have additional roles as HVA has recently been found to selectively activate the honey bee DA receptor, AmDOP3 (Beggs and Mercer 2009). …”
Section: Pheromone Effects On Behaviour and Physiology-how Are They Mmentioning
confidence: 99%
“…QMP, and HVA alone, have subsequently been shown to reduce DA levels in young worker bees and QMP transiently alters levels of DA receptor gene expression in the brain (Beggs et al 2007). In an experiment in which DA receptors were expressed in vitro, HVA was found to selectively activate AmDOP3 receptors while having no effect on the two other honey bee DA receptors, AmDOP1 and AmDOP2 (Beggs and Mercer 2009). As the dose at which HVA showed an effect on heterologously expressed AmDOP3 receptors was rather high (~10 μM range) in comparison to the concentration detected in QMP, further studies are required to confirm that AmDOP3 receptors in vivo are activated by the pheromone.…”
Section: Qmp Affects Da Signalling In the Beementioning
confidence: 99%